Narratives of neoliberalism: 'clinical labour' in context. Issue 1 (7th June 2015) - Parry, Bronwyn
Abstract : Cross-border reproductive care has been thrust under the international spotlight by a series of recent scandals. These have prompted calls to develop more robust means of assessing the exploitative potential of such practices and the need for overarching and normative forms of national and international regulation. Allied theorisations of the emergence of forms of clinical labour have cast the outsourcing of reproductive services such as gamete donation and gestational surrogacy as artefacts of a wider neoliberalisation of service provision. These accounts share with many other narratives of neoliberalism a number of key assertions that relate to the presumed organisation of labour relations within this paradigm. This article critically engages with four assumptions implicit in these accounts: that clinical labourers constitute a largely homogeneous underclass of workers; that reproductive labour has been contractualised in ways that disembed it from wider social and communal relations; that contractualisation can provide protection for clinical labour lessening the need for formal regulatory oversight; and that the transnationalisation of reproductive service labour is largely unidirectional and characterised by a dynamic of provision in which 'the rest' services 'the West'. Drawing on the first findings of a large-scale ethnographic research project into assisted reproduction in India I provide evidence to refute these assertions. In so doing the article demonstrates that while the outsourcing and contractualisation of reproductive labour may be embedded in a wider neoliberal paradigm these practices cannot be understood nor their impacts be fully assessed in isolation from their social and cultural contexts.